The given equation can be written as
(D2+D-2)y = -6 sin2x -18cos2x
The auxiliary equation of the above is
D2 +D-2=0
D = 1,-2
The complimentary solution is given by:
y= c1 ex + c2 e-2x
Particular solution is given by:
"\\frac{1}{D^2+D-2}( -6sin2x -18cos2x )="
"=\\frac{1}{D^2+D-2} (-6sin2x)-\\frac{1}{D^2+D-2}(-18cos2x)"
"=\\frac{-6sin2x}{D-6} - \\frac{18cos2x}{D-6}"
"= (D+6) \\frac{-6sin2x}{D^2-36}-(D+6) \\frac{18cos2x}{D^2-36}"
"=(D+6) \\frac{-6sin2x}{-40} -(D+6) \\frac{18cos2x}{-40}"
"=\\frac{3}{10}(cos2x+3sin2x) + \\frac{9}{10} (-sin2x+3cos2x)"
=3 cos2x
So, the solution is y= c1 ex+ c2e-2x + 3 cos2x
Now, initial conditions given are:
y(0)=2
-1=c1+c2
y' = c1ex -2c2e-2x -6 sin2x
y'(0)=2
2= c1-2c2
c1=0 , c2=-1
y=-e-2x +3cos2x
Comments
Leave a comment